Scattering parameter methods for calculating envelope correlation coefficient in multiple sensors configuration - Mohd Nor Azami, Mohd Adzimnuddin; Abd. Aziz, Mohamad Zoinol Abidin; Ja'afar, Abd Shukur (2024)
The Envelope Correlation Coefficient (ECC) is a critical parameter in evaluating the performance of multiple sensors systems, particularly in wireless communication, sensing, and microwave imaging applications. ECC quantifies the degree of similarity between the signals received or transmitted by difference sensors within a system. A higher ECC value (closer to 1.00) indicates strong correlation, meaning the sensors receive highly similar signal. In addition to ECC, the efficiency of power transmission and reception, as well as the implementation of multiband path transmission, play significant roles in the overall performance of sensor networks. Multiband path transmission allows for the use of multiple frequency bands, enhancing data rate and reliability by mitigating interference and maximizing bandwidth utilization. Calculating ECC using Scattering parameter for four difference sensors and three set of configurations has been studied. The measurement for the Scattering Parameter has given an accurate result and Configuration B shows the highest correlation for all sensors which is valued close at 1.00. This result shows that the configuration has a good sensing element, suitable to employ in detection and sensing element